Drove roads as local biodiversity reservoirs: effects on landscape pattern and plant communities in a Mediterranean region - Azcárate, Francisco M.; Robleño, Irene; Seoane, Javier; Manzano, Pablo; Peco, Begoña (Applied Vegetation Science, 2012)
Question: What are the effects of traditional drove roads on landscape pattern and plant communities? Location: Madrid Autonomous Region, Central Spain. Methods: We selected four study localities in different landscape units. Within each locality, we selected eight sites and within each site, we established three 1-ha plots, each corresponding to one of three situations: drove road, adjacent matrix or distant matrix. The landscape pattern of each plot was characterized by the cover of the different patch types, the patch type richness ha 1 and the patch type evenness ha 1 . At one site per locality, we also recorded vegetation by randomly distributing twenty 20 cm 9 20 cm quadrats per plot. We characterized each quadrat by its species richness, plant species composition and plant functional composition. We also analysed species richness by constructing rarefaction curves for each plot. Results: In the localities situated in croplands, sub-mediterranean forests and coniferous forests, drove roads were found to be an important source of spatial heterogeneity and a reservoir for a large number of plant species. In contrast, drove roads did not differ from the matrix habitats in rangelands, suggesting that the processes shaping drove road vegetation are similar to the general processes that shape grazed systems. Drove roads did not imply a signiﬁcant increase in functional diversity. Our results were heavily scale-dependent: while drove roads provided heterogeneity at the local scale, they showed a remarkable similarity at the large scale. Conclusions: Drove roads act as authentic local biodiversity reservoirs, especially in environments with low grazing levels. At the same time, drove roads imply structural and functional continuity on a large scale, increasing potential connectivity at the regional level. We recommend the preservation of drove roads in a functional state, because of their beneﬁts to plant biodiversity conservation, and claim that these beneﬁts should be considered when designing livestock policies with different intensiﬁcation scenarios.
Keywords: extensive grazing; functional diversity; functional traits; landscape heterogeneity; Transhumance

The role of land abandonment in landscape dynamics in the SPA ‘Encinares del rı́o Alberche y Cofio, Central Spain, 1984–1999 - Romero-Calcerrada, Raúl; Perry, George L W (Landscape and Urban Planning, 2004)
Land use has changed dramatically over the last 30–40 years throughout the Mediterranean. Much of this change has been driven by shifts in agricultural and socio-economic policy. This paper explores landscape dynamics in the SPA ‘Encinares del r´ıo Alberche y Coﬁo’ Central Spain between 1984 and 1999 in an area of approximately 83,000 ha. Categorical land cover maps, derived from three (1984, 1991 and 1999) remotely sensed Landsat images, are analyzed using a suite of landscape pattern metrics, and a simple transition matrix model of landscape change is developed. As with other landscapes in the Mediterranean a key trend is that of the abandonment of agricultural land and its subsequent succession to scrubland and woodland. Although there were signiﬁcant composition changes in the landscape over the study period conﬁgurational changes are less evident. The transition matrix model suggests that there were differences in landscape dynamics between 1984–1991 and 1991–1999—most importantly an increase in the rate of land abandonment is evident. The model predicts a steady state landscape containing a higher abundance of scrubland and woodland, and a corresponding decline in pastureland and cropland. Finally, the underlying socio-economic and other drivers of landscape change in the Encinares del r´ıo Alberche y Coﬁo and some of the implications of recent changes are discussed in terms of increased wildﬁre risk. Sustainable management of landscapes to protect biodiversity requires the type of study described here. A necessary pre-requisite of such management activities or planning is an assessment of changes in landscape pattern and process, the social and economic pressures driving them, and their possible effects on ecosystem structure and function.
Keywords: Central Spain; Human disturbance; Land abandonment; landscape change; landscape heterogeneity; landscape metric; special protection areas (spa); transition matrix model

The role of land abandonment in landscape dynamics in the SPA ‘Encinares del rı́o Alberche y Cofio, Central Spain, 1984–1999 - Romero-Calcerrada, Raúl; Perry, George L. W. (Landscape and Urban Planning, 2004)
Land use has changed dramatically over the last 30–40 years throughout the Mediterranean. Much of this change has been driven by shifts in agricultural and socio-economic policy. This paper explores landscape dynamics in the SPA ‘Encinares del r´ıo Alberche y Coﬁo’ Central Spain between 1984 and 1999 in an area of approximately 83,000 ha. Categorical land cover maps, derived from three (1984, 1991 and 1999) remotely sensed Landsat images, are analyzed using a suite of landscape pattern metrics, and a simple transition matrix model of landscape change is developed. As with other landscapes in the Mediterranean a key trend is that of the abandonment of agricultural land and its subsequent succession to scrubland and woodland. Although there were signiﬁcant composition changes in the landscape over the study period conﬁgurational changes are less evident. The transition matrix model suggests that there were differences in landscape dynamics between 1984–1991 and 1991–1999—most importantly an increase in the rate of land abandonment is evident. The model predicts a steady state landscape containing a higher abundance of scrubland and woodland, and a corresponding decline in pastureland and cropland. Finally, the underlying socio-economic and other drivers of landscape change in the Encinares del r´ıo Alberche y Coﬁo and some of the implications of recent changes are discussed in terms of increased wildﬁre risk. Sustainable management of landscapes to protect biodiversity requires the type of study described here. A necessary pre-requisite of such management activities or planning is an assessment of changes in landscape pattern and process, the social and economic pressures driving them, and their possible effects on ecosystem structure and function.
Keywords: Central Spain; Human disturbance; Land abandonment; landscape change; landscape heterogeneity; landscape metric; special protection areas (spa); transition matrix model

The role of landscape structure in species richness distribution of birds, amphibians, reptiles and lepidopterans in Mediterranean landscapes - Atauri, J A; Lucio, J V De (Landscape ecology, 2001)
The parameters referring to landscape structure are essential in any evaluation for conservation because of the relationship that exists between the landscape structure and the ecological processes. This paper presents a study of the relationships between landscape structure and species diversity distribution (estimated in terms of richness of birds, amphibians, reptiles and butterﬂies) in the region of Madrid, Spain. The results show that the response of species richness to landscape heterogeneity varies depending on the group of species considered. For birds and lepidopterans, the most important factor affecting the distribution of richness of species is landscape heterogeneity, while other factors, such as the speciﬁc composition of land use, play a secondary role at this scale. On the other hand, richness of amphibians and reptiles is more closely related to the abundance of certain land-use types. The study highlights the importance of heterogeneity in Mediterranean landscapes as a criterion for landscape planning and for deﬁnition of management directives in order to maintain biodiversity
Keywords: diversity distribution; landscape ecology; landscape heterogeneity; species richness distribution

The role of landscape structure in species richness distribution of birds, amphibians, reptiles and lepidopterans in Mediterranean landscapes - Atauri, J. A.; Lucio, J. V. De (Landscape ecology, 2001)
The parameters referring to landscape structure are essential in any evaluation for conservation because of the relationship that exists between the landscape structure and the ecological processes. This paper presents a study of the relationships between landscape structure and species diversity distribution (estimated in terms of richness of birds, amphibians, reptiles and butterﬂies) in the region of Madrid, Spain. The results show that the response of species richness to landscape heterogeneity varies depending on the group of species considered. For birds and lepidopterans, the most important factor affecting the distribution of richness of species is landscape heterogeneity, while other factors, such as the speciﬁc composition of land use, play a secondary role at this scale. On the other hand, richness of amphibians and reptiles is more closely related to the abundance of certain land-use types. The study highlights the importance of heterogeneity in Mediterranean landscapes as a criterion for landscape planning and for deﬁnition of management directives in order to maintain biodiversity
Keywords: diversity distribution; landscape ecology; landscape heterogeneity; species richness distribution